Contribuição ao planejamento de trajetória de robôs através de elementos de dinâmica, controle e otimização - Santos, Rogério Rodrigues dos (2007)
Robotic manipulators are programmable devices designed to execute a great variety of tasks in a repetitive way. In industrial environments, the reduction of dynamic requirements associated to a specific task can result in productivity increase and cost reduction regarding the robotic operation and maintenance. Moreover, the reduction of such requirements can enable the execution of tasks that demand the maximum performance of the system, increasing the robot versatility to be adapted to several situations. In operations involving repetitive tasks, for which time has to be optimally used, reducing the time necessary to perform a specific movement can also result in a significant increase of productivity. In this work several off-line strategies to compute the robot inverse kinematics and robot path planning are presented, taking into account the traveling time, kinematic and dynamic characteristics, and obstacle avoidance, as performance indexes to be optimized. It is also presented a strategy for optimal task repositioning into the workspace, thus decreasing the required mechanical power and associated vibration. Also, an on-line path planning strategy for mobile robots is studied. Objective functions are proposed to each case, exploring the solution through nonlinear programming, multicriteria programming and optimal control theories. A number of numerical results show the viability of the methodologies proposed.